2017
DOI: 10.1111/acer.13432
|View full text |Cite
|
Sign up to set email alerts
|

Varenicline Reduces Alcohol Intake During Repeated Cycles of Alcohol Reaccess Following Deprivation in Alcohol‐Preferring (P) Rats

Abstract: Background Most alcoholics experience periods of voluntary alcohol abstinence or imposed alcohol deprivation followed by a return to alcohol drinking. The current study examined whether varenicline (VAR) reduces alcohol intake during a return to drinking after periods of alcohol deprivation in rats selectively bred for high alcohol drinking (the alcohol preferring or “P” rats). Methods Alcohol-experienced P rats were given 24-hour access to food and water and scheduled access to alcohol (15% and 30% v/v) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
18
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 52 publications
6
18
2
Order By: Relevance
“…NTX and BUP, expressed as free base masses, were added to the gelatin solution to provide the following doses: 10.0 mg of NTX/3.0 ml solution/kg BW, 10.0 mg or 20.0 mg BUP/3.0 ml solution/kg BW, and 10.0 mg NTX + 10.0 mg BUP/3.0 ml solution/kg BW. While still hot, the gelatin solution containing the drug(s) was aliquoted into star shaped molds with the volume of each aliquot determined by the final concentration of the gelatin (mg drug/ml of gelatin solution) and the BW of the animal in order to produce individual drug doses, 1 dose per day per rat, as previously described (Froehlich et al, 2013a, 2013b, 2016, 2017a, 2017b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…NTX and BUP, expressed as free base masses, were added to the gelatin solution to provide the following doses: 10.0 mg of NTX/3.0 ml solution/kg BW, 10.0 mg or 20.0 mg BUP/3.0 ml solution/kg BW, and 10.0 mg NTX + 10.0 mg BUP/3.0 ml solution/kg BW. While still hot, the gelatin solution containing the drug(s) was aliquoted into star shaped molds with the volume of each aliquot determined by the final concentration of the gelatin (mg drug/ml of gelatin solution) and the BW of the animal in order to produce individual drug doses, 1 dose per day per rat, as previously described (Froehlich et al, 2013a, 2013b, 2016, 2017a, 2017b).…”
Section: Methodsmentioning
confidence: 99%
“…In our early work, drugs were delivered via injection and the duration of drug treatment was necessarily short. In order to reduce the stress of drug administration, and allow for prolonged drug treatment, we developed an oral drug delivery approach for rodents that is analogous to the way that drugs are delivered to humans (Froehlich et al, 2013a, 2013b, 2016, 2017a, 2017b; Rasmussen et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies examining Var and EtOH intake appear to conflict with the present findings. For example, treatment with 2 mg/kg Var reduced EtOH self-administration to ~1.5 g/kg/2-hour session following scheduled access and repeated cycles of deprivation (Froehlich et al 2016(Froehlich et al , 2017Czachowski et al, 2018). A number of factors contribute to these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the varenicline-induced decrease in nicotine intake observed here is consistent with previous preclinical results (Funk et al, 2016; Maggio et al, 2018; Scuppa et al, 2015). Although several preclinical studies have shown decreases in EtOH consumption following pretreatment with varenicline (Czachowski et al, 2018; Froehlich et al, 2017; Steensland et al, 2007), those studies only examined EtOH consumption in the absence of nicotine. Overall, preclinical evidence provides limited support for varenicline’s efficacy as a pharmacotherapeutic for co-users of EtOH and nicotine.…”
Section: Discussionmentioning
confidence: 99%